APPLICATION OF RENEWABLE ENERGY SOURCES IN THE CONDITIONS OF KASHKADARYA REGION - Мирзоев Зоир Сапаралиевич; Хайриддинов Шавкат Батирович (Modern American Journals, 2025)
The article highlights the available resources of renewable energy sources (solar and wind energy, biogas technology) in the Kashkadarya region and the possibilities of their use.
Keywords: Energy balance, renewable energy sources, hydropower, wind energy, geothermal energy, biomass, solar heat supply, solar electricity supply.